Assessment and adaptive management of Orange Roughy off Southern Africa - Branch, Trevor (Department of Biological Sciences, 2024)
[page 122, 123, 124 missing] Exploratory fishing off southern Africa for deepwater fish species (at depths > 500 m) started in earnest in 1994. The most sought· after of these species is the orange roughy (Hoplostethus atlanticus), which has provided the basis for lucrative trawl fisheries in New Zealand and Australia. Orange roughy form dense aggregations, especially during the spawning season, from which catch rates may reach 50 tonnes per minute of trawling with the net on the seabed. Orange roughy have many features of a K-selected species: extreme longevity(> 100 years), slow growth rate, low fecundity and poor productivity, although some of these estimates are controversial. All of these factors conspire to make orange roughy easily susceptible to over-fishing. Discoveries of fishable aggregations of orange roughy were made off Namibia in January J 995. In a short period of time, the annual catch became the second greatest in the world after New Zealand, and management advice for this fishery was urgently needed. In the absence (at that time) of scientific surveys that typify management in the more established fisheries off Australia and New Zealand, another approach was needed at the onset of the fishery: A swept-area methodology was developed which could be applied to the available commercial data. Swept-area biomass estimates were made and then corrected for the most factors thought to introduce bias, for example adjustment for the directed nature of the commercial data. Open discussion was held during two meetings in Namibia in January 1997 to decide on the values for these bias factors. Representatives of the exploratory fishing company and the Namibian fisheries ministry, and two international scientists were present at these meetings. Two final sets of specifications gave median biomass estimates of 306 000 t (CV = 34%) and 321 000 t (CV= 29%). An estimated 38-42% of this biomass was found inside four high-density aggregations, while the remainder was sparsely distributed around the Namibian coast